THE EFFECT OF ADDING DIFFERENT AMOUNT OF SAGO FLOUR FOR THE QUALITY OF REBON SHRIMP SILAGE (Acetes erythraeus) - Daffa Ramadhan; Dewita Dewita; Suparmi Suparmi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Silage can be produced in two ways, namely chemically and biologically, followed byfermentation. Biological silage production is a fermentation process that utilizes certain microbes (lacticacid bacteria) by adding carbohydrate sources. The lack of carbohydrate content in fresh rebon shrimp canbe added sago flour as a source of carbohydrates. The study aimed to determine the effect and amount ofaddition of the best sago flour on the quality of rebon shrimp silage. The method used in this research wasexperimental method, namely conducting to produce rebon shrimp (Acetes erythraeus) silage using 10%L. plantarum bacteria of the weight of rebon shrimp used. The treatment used was the addition of differentamounts of sago flour of which consisted of 4 treatment levels, each: P1 (10%), P2 (20%), P3 (30%), andP4 (40%). The experimental design used was a non-factorial Completely Randomized Design (CRD) with3 replications. Data from observations were analyzed using ANOVA test and Turkey’s HSD test, each at a99% confidence level. The best treatment was P4 with proximate including: 17.13% protein content,0.95% fat, 74.02% water, and 1.08% ash. Furthermore, the pH value was 4.7 and the total lactic acidbacteria was 1.36 x 107 cfu/mL. Eventually, the addition of different amounts of sago flour can increasethe quality of rebon shrimp silage.